Antiviral effects of the petroleum ether extract of Tournefortia sibirica L. against enterovirus 71 infection in vitro and in vivo - Huang, Xinyu; Li, Jiemin; Hong, Yan; Jiang, Chenghan; Wu, Jiaxin; Wu, Min; Sheng, Rui; Liu, Hongtao; Sun, Jie; Xin, Ying; Su, Weiheng (Frontiers in Pharmacology, 2022)
Enterovirus 71 (EV71) is the major cause of severe hand, foot, and mouth disease (HFMD). Compared to other HFMD pathogens, like coxsackievirus A16 (CVA16), EV71 can invade the central nervous system and cause permanent damage. At present, there are no available antivirals against EV71 for clinical treatment. Herein, multiple Chinese botanical drugs were collected, and 47 types of botanical extracts were extracted using aqueous solutions and organic solvents. Based on the cytopathic effect inhibition assay, petroleum ether extract of Tournefortia sibirica L. (PE-TS) demonstrated 97.25% and 94.75% inhibition rates for EV71 infection (at 250 μg/ml) and CVA16 infection (at 125 μg/ml), respectively, with low cytotoxicity. Preliminary mechanistic studies showed that PE-TS inhibits replication of EV71 genomic RNA and synthesis of the EV71 protein. The released extracellular EV71 progeny virus titer decreased by 3.75 lg under PE-TS treatment. Furthermore, using a newborn mouse model, PE-TS treatment protected 70% and 66.7% of mice from lethal dose EV71 intracranial challenge via administration of intraperitoneal injection at 0.4 mg/g and direct lavage at 0.8 mg/g, respectively. The chemical constituents of the PE-TS were analyzed by Gas Chromatography-Mass Spectrometer (GC-MS), and a total of 60 compounds were identified. Compound-target network analysis and molecular docking implied potential bioactive compounds and their protein targets against EV71 associated pathology. The present study identified antiviral effects of PE-TS against EV71/CVA16 infection in vitro and EV71 infection in vivo, providing a potential antiviral botanical drug extract candidate for HFMD drug development.